PREVENTION OF EARLY MARRIAGE IN REDUCING THE LEVEL OF VIOLENCE AGAINST WOMEN IN GORONTALO REGENCY - Umar, Aprilia; Walahe, Dewi (Universitas Gorontalo, 2020)
Data from the Gorontalo Regional Police on cases of violence against women in 2015 were 212. While the number of violence against children was even more worrying, namely 423 cases, consisting of 232 sexual crimes against children, 181 physical violence and 41 cases of psychological violence. The purpose of this study was to determine efforts to prevent early marriage that have been carried out by the Office of Women's Empowerment and Child Protection in Gorontalo District against female violence and to determine the effect of early marriage prevention on the level of violence on women. The location of this research is the Women's Empowerment and Child Protection Agency. This research uses descriptive qualitative research methods. The results of this study are the efforts made by the Women's Empowerment and Child Protection Agency to prevent early marriage in reducing the level of violence in women, namely through an integrated service center for women and children empowerment, the Task Force Team for Violence against Women and Children, Community-Based Integrated Protection, Socialization, Assistance and Use the Puspaga mobile application.